Acetamidinium Cation to Confer Ion Immobilization and Structure Stabilization of Organometal Halide Perovskite Toward Long Life and High‐Efficiency p‐i‐n Planar Solar Cell via Air‐Processable Method. Issue 9 (8th June 2020) - Hsiao, Kai-Chi; Jao, Meng-Huan; Tian, Kuo-Yu; Lin, Ting-Han; Tran, Dinh-Phuc; Liao, Hsueh-Chung; Hou, Cheng-Hung; Shyue, Jing-Jong; Wu, Ming-Chung; Su, Wei-Fang
Abstract : Ion migration in organometal halide perovskite solar cell (OHPSC) and crystal structure evolution of organometal halide perovskites (OHPVSKs) in air are considered as one of the critical factors for unstable performance and of the urgent issues for the reliability of OHPSCs. Herein, a novel cation of acetamidinium (Aa + ) with stronger coordinated bond with I − than methylammonium is induced into OHPVSK to stabilize its crystal structure. By incorporating Aa + ions into OHPVSKs, the power conversion efficiency (PCE) of OHPSC without an encapsulation can maintain higher than 75% of its initial PCE after a 200 h humidity (60–80% relative humidity (RH) in air) or a 24 h thermal stress test (85 °C in dry N2 ). The Aa–MAPbI3 device exhibits an outstanding efficiency of 20.68%, and over 80% of initial PCE is maintained after a 1300 h damp heat as encapsulated. This novel cation can be easily incorporated into OHPVSK via a hot casting process in air with a high environmental tolerance as compared with that from the conventional coating process, which suffers from sophisticated crystallization steps and a strict processing atmosphere. It extends processing windows for OHPVSK fabrication and provides a promising path toward mass production and further commercialization. Abstract : An environmentally stable acetamidinium (Aa + )‐incorporated MAPbI3 film is successfully fabricated via hot casting in air. The large Aa + immobilizes ions and improves crystal structure of MAPbI3 through strong coordination bonds. The corresponding Aa–MAPbI3 device shows 20.68% power conversion efficiency. Its 80% is maintained after 1300 h testing at 85 °C and 85 relative humidity (RH)%.